DETERMINANTS OF PRICE AND PRODUCT QUALITY ON THE PURCHASE DECISION OF CAR GLASS FILM - Muis, Muhammad Ras; Rianto, Slamet (International Proceeding of Law and Economic, 2021)
The purpose of this research is to find out and analyze the effect of price and product quality on the purchase decision of car window film at PT RVM Window Film - Medan, this study was 100 respondents. Test for 10 targeted 10 people / day the number of sampling in this study was 100 respondents. The data collection techniques in this study were questionnaire (questionnaire), interview (interview) and documentation study. The data analysis technique used is multiple linear regression by first testing the assumptions of kasik, t test, F test and the coefficient of determination. The results of the study show that the price significantly influences the purchase decision of car window film at PT RVM Window Film - Medan. Product quality significantly influences the purchase decision of car window film at PT RVM Window Film - Medan.